Information systems security : 15th International Conference, ICISS 2019, Hyderabad, India, December 16-20, 2019, Proceedings /: 15th International Conference, ICISS 2019, Hyderabad, India, December 16-20, 2019, Proceedings. (2019) - Unknown
No abstract available